Valuation of companies through discounted cash flow: case study - Molina Panchi, Diego Fabián (2024)
Today organizations must adapt to various scenarios that positively and negatively influence economic-financial performance, so they must rethink their business management model with a focus on mitigating uncertainty and taking advantage of their potential strengths. However, in essence, the valuation of companies estimates the degree of subjectivity, since there is no method that allows to accurately measure the real value of a company. Similarly, value is a term used in economics that seeks to quantify the benefits obtained in the present and in the future through static and dynamic methods. Likewise, the objective of the investigation is to establish the real amount of a business case study through the discounted cash flow valuation method to determine its intrinsic value. In this sense, the research focus is focused on the use of quantitative variables and financial evaluation tests. On the other hand, the type of research is descriptive and due to its design, it is not experimental of a longitudinal type. The results show the following: the average financial value of the company is above the investment and an insignificant risk value. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/2442